Rodzicielska membrana i domowa kultura cyfrowa. Przypadek pokolenia Alfa - Ogonowska, Agnieszka (Studia Edukacyjne, 2025)
Comparative studies on Generation Alpha and Generation Z in Poland reveal both intergenerational differences in the use of digital technologies and the influence of the family environment on the formation of domestic digital culture. The structured interviews carried out as a part of original research focusing on representatives of Generation Alpha uncovered diverse models of digital socialization within families, ranging from restrictive to participatory models. The findings indicate that domestic media practices vary significantly depending on socio-economic factors and the level of parents’ digital competence. In the context of glocalization, these studies show how global technological trends are adapted to local family conditions, leading to heterogeneous patterns of digital media usage among representatives of Generation Alpha.